JARING PATRIARKI: CERPEN JARING-JARING MERAH KARYA HELVY TIANA ROSA MELALUI FEMININE MYSTIQUE BETTY FRIEDAN - Ridho Sastro Panjaitan; Tabita Tesalonika Simaremare; Grace Evelyn Hutabarat; Irfansyah Barus; Jakaria Jakaria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the depiction of patriarchy in Helvy Tiana Rosa's short story "Jaring Merah" through the perspective of Betty Friedan's Feminine Mystique. This short story features a female character trapped within a patriarchal social construct, experiencing restricted movement, psychological violence, and exclusion from public spaces. This study employs a feminist literary criticism approach, using Friedan's Feminine Mystique to analyze how women's identities are constrained by the demands of domestic roles imposed by the patriarchal system. The method used is qualitative descriptive with textual analysis techniques. The research findings indicate that the female character in this short story faces what Friedan calls "the problem that has no name," namely, identity confusion resulting from the absorption of patriarchal values ​​that hinder women's freedom and potential. This research contributes to the development of feminist literary studies in Indonesia and raises critical awareness of gender-based violence hidden within sociocultural norms.